Implementation of The Law on Information and Electronic Transactions and Pancasila Law Enforcement Related to Cybercrimes in Indonesia - Hartati, Sri; Karyono, Hadi; Karno Sabowo, Hudi (CV. Inara, 2022)
Information technology has a very important role, both now and in the future. In reality, although there are a number of laws and regulations that prohibit hate speech in public spaces, there are still few people who realize that this act is a violation of the law, not only the perpetrators but also the victims and even the officers. This journal aims to find out the implementation of Law No.19 of 2016 concerning Information and Electronic Transactions in the development of criminal crimes that occur in Indonesia, especially in cybercrimes. The author intends to directly describe social phenomena based on indicators whether or not the phenomenon under study regarding the implementation of the Law on Information and Electronic Transactions and Pancasila regarding law enforcement related to cybercime in Indonesia is currently happening. Therefore, it is the joint responsibility of the government, law enforcement officers/Polri and TNI as well as all elements of society to combat the turmoil of cyber crime, SARA, etc., based on relevant legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. The basis for law enforcement that can answer the demands of society must be responsive law, otherwise the law will lose its spirit. Morals and justice are the spirit of the law. Legal reform must look back at the solidity of morality that lives, grows and develops in society. Against this note, the author views that the choice of revision of the Law on Information Electronic and Transactions does not have to come from the DPR. The President as one of the law-forming institutions, based on the provisions of Article 5 paragraph (1) of the 1945 Constitution of the Republic of Indonesia is also authorized to propose revisions to the Law Information and Electronic Transactions which urgently needs to be carried out.